2016
DOI: 10.1021/acs.bioconjchem.6b00241
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Responsive, Tumor Penetrating Lipid Nanoparticles for Delivery of Chemotherapeutics to Pancreatic Cancer Cell Spheroids

Abstract: Solid tumors are often poorly irrigated due to structurally compromised microcirculation. Uncontrolled multiplication of cancer cells, insufficient blood flow, and the lack of enough oxygen and nutrients lead to the development of hypoxic regions in the tumor tissues. As the partial pressure of oxygen drops below the necessary level (10 psi), the cancer cells modulate their genetic makeup to survive. Hypoxia triggers tumor progression by enhancing angiogenesis, cancer stem cell production, remodeling of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 24 publications
0
51
0
Order By: Relevance
“…Our hypothesis was based on the fact that such programmed disintegration of larger nanoparticles will provide with deeper penetration of drug‐transporting nanocarriers through the dense desmoplastic microenvironment of pancreatic cancer. We selected pH as the stimulus to trigger such controlled destabilization because for PDAC and any other form of solid tumors, pH decreases sharply in conjunction with low O 2 tension as the distance increases from blood vessels to tumor tissues . In addition, smaller nanoparticles are required to penetrate deep‐seated tumor cells and cancer‐like stem cells, many of which are difficult to reach with larger nanoparticles due to altered microvasculature present in solid tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Our hypothesis was based on the fact that such programmed disintegration of larger nanoparticles will provide with deeper penetration of drug‐transporting nanocarriers through the dense desmoplastic microenvironment of pancreatic cancer. We selected pH as the stimulus to trigger such controlled destabilization because for PDAC and any other form of solid tumors, pH decreases sharply in conjunction with low O 2 tension as the distance increases from blood vessels to tumor tissues . In addition, smaller nanoparticles are required to penetrate deep‐seated tumor cells and cancer‐like stem cells, many of which are difficult to reach with larger nanoparticles due to altered microvasculature present in solid tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent hydrolysis and reduction generates a shorter peptide with high affinity for the neuropilin receptors and tissue penetration capability . Nanoparticles conjugated to the iRGD peptide have been observed to penetrate into the tumors and deliver the drugs . In an in vivo study, the chemotherapeutic drugs showed better efficacy when co‐administered with the iRGD peptide .…”
Section: Figurementioning
confidence: 99%
“…We have used the iRGD peptide to enhance the tumor penetration of liposomes in the tumor tissues . However, polymersomes are considerably more stable compared to the liposomes, and offer better membrane stability with reduced drug release in the absence of stimulus .…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations